Фразеалагізмы і парэміі ў кнізе Аляксея Дзікавіцкага Oньдэ - Каліта, Іна (Slavia Orientalis, 2025)
The article combines two main directions in the study of stable phrasems and paremies: (1) stable units as an individual-author's tool and the building material for a literary work, (2) West Polesian phrasems against the background of Belarusian and, more broadly, general Slavic phraseological and paremies collections. The article examines stable units of various types from Aliaksey Dzikavitsky's book Oñde, written in the Pinsk variant of the West Polesian dialect. The analysis is based on a sampling of about 120 stable collocations, including proverbs and phrasal units. The main thematic groups of phrasems are identified: units with the component God, world, units that convey the semantics of 'human qualities,' 'drunkenness,' 'work,' 'death,' 'large quantity, and distinctive units with a uniquely Polesian flavour. The analysis shows that collocations are used by the writer as effective stylistically marked building material. With their help, the author creates vividly saturated constructions in which spoken polylogues sound natural, and compression contributes to the intensification of the emotional content. Phrasems and proverbs are used by the author as a means of enriching the characters language and solving the author's stylistic tasks.